Development and evaluation of a PCR assay for rapid detection of azithromycin resistant Campylobacter isolated from diarrhoeal patients in Kolkata, India - Mukherjee, Piyali (Gut Pathog, 2017)
BACKGROUND: Campylobacter is a well-known bacterial pathogen for triggering acute gastroenteritis in humans both in developed and developing countries. This organism is highly resistant to fluoroquinolones. Macrolides are very much useful for the treatment of campylobacteriosis when clinical therapy is necessary. However, increasing resistance to azithromycin, a potent macrolide has been reported in Campylobacter in recent years. Macrolide resistance in Campylobacter is found mainly due to point mutation in V region of 23S rRNA. RESULTS: We have developed a PCR based assay, which can detect the azithromycin resistant and sensitive Campylobacter strains utilizing mutation responsible for the phenotype. This PCR was validated using 359 Campylobacter strains isolated from diarrhoeal patients at Kolkata, India. Antimicrobial resistance through disk diffusion method was also performed on these strains as a gold standard. Studies through sequencing analysis further confirmed the PCR result. CONCLUSION: This study describes a simple and rapid method for detection of mutation conferring macrolide resistance with additional feature of identification of sensitive strains.